KONJUNGSI DALAM ALBUM 21 OLEH ADELE ADKINS - MULERU, ATIKA KARIATI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT This research entitled â€œConjunction in the Album 21 By Adele Adkinsâ€ is an attempt to found conjunction in terms of form, function and meaning in the songs. The purpose of this research is to describe, identify, and analyze the forms, functions and meaning of conjunctions in the songs. The theories used in this research are Aarts and Aarts (1982:44), John and Yates (1982:450), and Marcella Frank (1972:206). The investigation has been done through the library and field research. The data about conjunction in the songs are being collected from album 21 by Adele Adkins. The results shows that, there are nine simple conjunctions in the album 21 and those are and, if, that, but, or, until, for, as, why, yet, so and there are no findings for complex conjunction. In terms of function, there are coordinators and subordinators conjunction in the songs. Coordinators conjunction are and, but, or, yet, so and subordinators conjunction are that, as, for, until, if, why. In terms of the meaning of conjunction, the writer found 9 meanings from conjunction in the album 21 by Adele Adkins, there are conjunctions that shows the addition are and and yet, conjunction that shows the difference is but, conjunctions that shows cause and purpose are as and why, conjunction that cause requirement is if, conjunction indicates choices is or, conjunction that shows purpose is that, conjunction that show cause and result is for, conjunction that shows time is until and conjunction that shows the meaning of result is so. Â  Â  Keywords : Conjunction, Album Adele 21, form, function, meaning